The Kinetics and Mechanism of Atmospheric Corrosion Occurring on Tin and Iron-Tin Intermetallic Coated Steels: II. Filiform Corrosion - Geraint Williams (Journal of The Electrochemical Society, 2016)
This paper describes a systematic study into the initiation and propagation of filiform corrosion (FFC) on pure iron, pure tin and industrially important tin and iron-tin intermetallic (FeSn and FeSn2) coatings for packaging steels, as a function of coating weight. The time-dependent extent of FFC was determined optically. FFC was not observed on pure tin or tin coatings but was found to propagate at significantly reduced rates on the FeSn and FeSn2 intermetallic coatings, when compared to pure iron. An explanation of the findings is given, firstly, in terms of the open circuit potential (OCP) and the extent to which polarity of the galvanic corrosion cell formed between relevant phases permits FFC propagation, and secondly in terms of the relative susceptibility of the various phases to anodic dissolution. It is concluded that even when FFC is feasible thermodynamically, propagation rates may be negligible due to the low activity for anodic dissolution of tin and iron-tin intermetallics.